2003
DOI: 10.4049/jimmunol.170.4.1939
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Intracellular Survival ofMycobacterium tuberculosisin Human Dendritic Cells

Abstract: Dendritic cells (DCs) are likely to play a key role in immunity against Mycobacterium tuberculosis, but the fate of the bacterium in these cells is still unknown. Here we report that, unlike macrophages (Mφs), human monocyte-derived DCs are not permissive for the growth of virulent M. tuberculosis H37Rv. Mycobacterial vacuoles are neither acidic nor fused with host cell lysosomes in DCs, in a mode similar to that seen in mycobacterial infection of Mφs. However, uptake of the fluid phase marker dextran, and of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 63 publications
(74 reference statements)
12
119
0
4
Order By: Relevance
“…Changes in the transcriptome following MTB infection are expected to reflect the transition of DCs from antigen-capturing cells to potent antigen-presenting cells and T-cell activators (19,20). Consistent with this notion, we found that the maturation of DCs after MTB infection was accompanied by the strong upregulation of genes involved in immune responses (FDR < 10 −26 ), including cytokine signaling, T-cell activation, and antigen presentation (FDR < 0.006; Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Changes in the transcriptome following MTB infection are expected to reflect the transition of DCs from antigen-capturing cells to potent antigen-presenting cells and T-cell activators (19,20). Consistent with this notion, we found that the maturation of DCs after MTB infection was accompanied by the strong upregulation of genes involved in immune responses (FDR < 10 −26 ), including cytokine signaling, T-cell activation, and antigen presentation (FDR < 0.006; Fig.…”
Section: Resultssupporting
confidence: 73%
“…1B and Dataset S2). This observation probably reflects a reduced capacity of mature DCs to endocytose/phagocytose and the expected reduction in trafficking between the mycobacterial phagosome and the host cell recycling and biosynthetic pathways (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…Mtb is capable of replicating within DCs (Förtsch et al ., 2000), and some reports show that Mtb actually manipulates DC function and impairs their ability to control infection (Hanekom et al ., 2003). However, other studies find that DCs are beneficial to bolster the cellular immune response (Tailleux et al ., 2003). …”
Section: Cells Involved In the Innate Immune Response To Tb In Humansmentioning
confidence: 99%
“…Luego de 5 días de infección, 45% a 65% de los fagosomas micobacterianos retuvieron la expresión de esta GTPasa; este hallazgo se ha asociado con acceso de los compartimentos a la vía de reciclaje y a nutrientes (expresión de transferrina), y se ha encontrado que estos fagosomas tienen además acceso a la vía biosintética (expresión de proteínas específicas del RE, calnexina y Grp78/BiP) y comunicación con la vía endocítica (mediante la adquisición de dextrán). Asimismo, estos macrófagos son permisivos para la replicación micobacteriana (91).…”
Section: Otras Rab Durante La Infección Micobacterianaunclassified